Symbiosis Identity: Islam, Culture (Urf) and Social Mobilization in Indonesia - Siregar, Muhammad Habibi; Alijanovich, Yuldashev Mansurjon (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This article demonstrates that the extraction of Islamic value must be coped with social mobilization in the current situation. Voicing the importance of Islamic identity is to deal with the threat of global identity due to preserving the normative value. This article proposes that Islamic identity as the ultimate instrument to face the current challenges. Islamic Identity took a special code for anyone to insert oneself involved reality. Contrary with the assumed concept of globalism that could dismantle the traditional relation symbols amid the ethnicity is perceived as the stabilizer of social disruption in digital era. Recently, ethnicity gets the limelight due the globalism to strengthen the cohesive traditional connection to emerge showy. This article brings proven evidence to show a strong relations of ethnicity with nationality and religious values, which defend the establishment of the social order in nations such as Indonesia. Furthermore, this article found that the recent phenomena within the democracy system is to intake the dominant ethnic as the patron in politics, society, or religion. However, it is harnessed as potential threat to minorities’ identity in many fields.